Intracellular detection of differential APOBEC3G, TRIM5alpha, and LEDGF/p75 protein expression in peripheral blood by flow cytometry - Mous, Kim; Jennes, Wim; De Roo, Ann; Pintelon, Isabel; Kestens, Luc; Van Ostade, Xaveer (Journal of immunological methods, 2011)
Expression studies on specific host proteins predominantly use quantitative PCR and western blotting assays. In this study, we optimized a flow cytometry-based assay to study intracellular expression levels of three important host proteins involved in HIV-1 replication: apolipoprotein B mRNA-editing catalytic polypeptide-like 3G (APOBEC3G), tripartite motif 5alpha (TRIM5α), and lens epithelium-derived growth factor (LEDGF/p75). An indirect intracellular staining (ICS) method was optimized using antibodies designed for other applications like enzyme-linked immunosorbent assay (ELISA), confocal imaging, and western blotting. The median fluorescence intensity (MFI) value – a measure for the protein expression level – increased upon higher antibody concentration and longer incubation time, and was reduced following preincubation with recombinant proteins. Staining of stably transfected or knock-down cell lines supported the method's specificity. Moreover, confocal microscopy analysis of peripheral blood mononuclear cells (PBMC), when stained according to the ICS method, confirmed the localization of APOBEC3G and TRIM5α in the cytoplasm, and of LEDGF/p75 in the nucleus. Also, stimulation with mitogen, interferon-alpha, or interferon-beta resulted in detectable, albeit weak, increases in intracellular expression of APOBEC3G and TRIM5α. After optimization, the method was applied to healthy control and HIV-1 infected subjects. For all subjects studied, the memory subset of CD4+ T cells showed significantly higher expression levels of APOBEC3G, TRIM5α, and LEDGF/p75, while the CD16+ subset of monocytes was characterized by higher expression levels of LEDGF/p75. In addition, we observed that therapy-naïve HIV-1 patients tended to have lower expression levels of APOBEC3G and TRIM5α than HIV-1 negative controls. In summary, our data provide proof-of-principle for the detection of specific host factors at the level of a single cell, which may prove useful for our further understanding of their role in virus-host interactions. ► Flow cytometry-based method to study intracellular protein expression levels. ► Quantitative analysis of HIV-1-related proteins APOBEC3G, TRIM5α, and LEDGF/p75. ► Differential expression of APOBEC3G, TRIM5alpha, and LEDGF/p75 in PBMC subsets. ► Therapy-naive HIV-1 patients tend to express lower levels of APOBEC3G and TRIM5α. ► Interest to elucidate the role of specific host factors in virus-host interactions.